Neurochronometry of choice-induced preference changes: when do preferences actually change? - Davydova, Alina; Sheronova, Julia; Kosonogov, Vladimir; Shestakova, Anna; Klucharev, Vasily (Frontiers in Human Neuroscience, 2023)
According to cognitive dissonance theory, a discrepancy between preferences and actions may lead to the revaluation of preferences, increasing preference for the chosen options and decreasing for the rejected options. This phenomenon is known as the spreading of alternatives (SoA), which results in a choice-induced preference change (CIPC). Previous neuroimaging studies have identified several brain regions that play a role in cognitive dissonance. However, the neurochronometry of the cognitive mechanisms underlying CIPC is a topic of debate. In other words, does it occur during the difficult choice, immediately after the choice, or when people encounter the options again? Furthermore, it remains unclear what is the exact time point, relative to the onset of facing options, either within the choice or after it, when the attitudes start to be revised. We argue that applying online protocols of transcranial magnetic stimulation (TMS), during or immediately after the choice process, could be the most efficient way to better understand the temporal dynamics of the SoA effect. TMS allows for achieving high temporal and spatial resolution, modulating the activity of areas of interest, and examining the causal relationships. Besides, unlike the offline TMS, the online instrument allows tracking of the neurochronometry of attitude change, by varying stimulation onsets and durations with respect to the option stimuli. Based on scrupulous analysis of previous findings, employing online TMS studies of conflict monitoring, cognitive control, and CIPC neuroimaging results, we conclude that the use of online TMS is critical to examine the neurochronometry of CIPC.